2010
DOI: 10.3136/fstr.16.319
|View full text |Cite
|
Sign up to set email alerts
|

Denaturing Gradient Gel Electrophoresis Analysis of Lactic Acid Bacteria and Yeasts in Traditional Mongolian Fermented Milk

Abstract: We analyzed lactic acid bacteria (LAB) and yeast populations in samples of airag, undaa, and hoormog, which are varieties of traditional fermented milk produced in Mongolia. To effectively detect lactobacilli, lactococci/streptococci/enterococci, and leuconostocs for complete analysis of the complex LAB population in airag, we developed two new primer sets and examined these primer sets in three different combinations using denaturing gradient gel electrophoresis (DGGE). DGGE analysis revealed the diversity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…With respect to other species, it was also notable that Torulaspora delbreuckii was not detected in this study despite the fact that both it [10], [11] and its anamorph form, Candida colliculosa , have previously been detected in kefir [8]. There were also many instances whereby we identified species not previously detected in kefir milks, for instance while Dekkera anomala (anamorph: Brettanomyces anomalus ) has been isolated from kefir [8], Dekkera bruxellensis (anamorph: Brettanomyces bruxellensis ) has not been isolated from kefir before now (but has been found in traditional fermented Mongolean and Zimbabwean milks [64], [65]). Other species which had not previously been detected, but were present in lower abundance and few (often just one) milk sample(s) included Cryptococcus sp.…”
Section: Discussionmentioning
confidence: 85%
“…With respect to other species, it was also notable that Torulaspora delbreuckii was not detected in this study despite the fact that both it [10], [11] and its anamorph form, Candida colliculosa , have previously been detected in kefir [8]. There were also many instances whereby we identified species not previously detected in kefir milks, for instance while Dekkera anomala (anamorph: Brettanomyces anomalus ) has been isolated from kefir [8], Dekkera bruxellensis (anamorph: Brettanomyces bruxellensis ) has not been isolated from kefir before now (but has been found in traditional fermented Mongolean and Zimbabwean milks [64], [65]). Other species which had not previously been detected, but were present in lower abundance and few (often just one) milk sample(s) included Cryptococcus sp.…”
Section: Discussionmentioning
confidence: 85%
“…Bacterial genomic DNA of the two strains was extracted and purified according to the lysozyme‐SDS (sodium dodecylsulfate) method as described in Miyamoto et al . (2010).…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, several other studies have reported high proportion of Lb. helveticus in koumiss (Uchida et al, 2007;Watanabe et al, 2008;Wu et al, 2009;Miyamoto et al, 2010;Sun et al, 2010 a;Yu et al, 2011). The reason for this difference is unclear and merits further investigations.…”
Section: Discussionmentioning
confidence: 84%
“…Based on this fact, various independent cultivation methods have been developed during the last two decades (Theron and Cloete, 2000;Jany and Barbier, 2008;Pogacic et al, 2010). During the last decade, numerous studies have evaluated the bacterial communities of fermented milk products using PCR-denaturing gradient gel electrophoresis (PCR-DGGE) but less information is available on fermented milk products from Inner Mongolia and Mongolia (Hao et al, 2010;Miyamoto et al, 2010;Liu et al, 2012). Furthermore, minor knowledge is accessible on the construction of 16S rRNA clone libraries to evaluate the microbial communities of untreated and treated milk products (Callon et al, 2007;Rasolofo et al, 2010;Raats et al, 2011;Osvik et al, 2013).…”
Section: Introductionmentioning
confidence: 97%